2017
DOI: 10.1007/s11764-017-0645-9
|View full text |Cite
|
Sign up to set email alerts
|

An international review and meta-analysis of prehabilitation compared to usual care for cancer patients

Abstract: Purpose The purpose of the study is to systematically review and synthesise randomised controlled trials investigating the effectiveness of prehabilitation compared to usual care for newly diagnosed, adult-onset cancer patients. Methods MEDLINE, EMBASE, PsycINFO, CINAHL and SSCI were searched up to April 2017. Studies were included if disease-related, treatment-related, patient-reported and health service utilisation outcomes were assessed. Two reviewers independently reviewed and appraised the risk of bias of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(82 citation statements)
references
References 43 publications
6
70
0
6
Order By: Relevance
“…The authors suggest stress management training may be more effective in improving quality of life than psychotherapeutic approaches; however, as there is considerable variation in outcome measures, such conclusions may be premature. A more recent review of 18 prehabilitation interventions in cancer patients identified some additional studies that included a psychological component . Both reviews note that the included studies tend to be small, at risk of bias and use a variety of outcome measures, making synthesis of the evidence difficult.…”
Section: Psychological Prehabilitation – a Cancer Focusmentioning
confidence: 99%
“…The authors suggest stress management training may be more effective in improving quality of life than psychotherapeutic approaches; however, as there is considerable variation in outcome measures, such conclusions may be premature. A more recent review of 18 prehabilitation interventions in cancer patients identified some additional studies that included a psychological component . Both reviews note that the included studies tend to be small, at risk of bias and use a variety of outcome measures, making synthesis of the evidence difficult.…”
Section: Psychological Prehabilitation – a Cancer Focusmentioning
confidence: 99%
“…In this context, a recent meta-analysis on 3257 patients with cancer indicated that moderate aerobic exercise performed at 70-80% of maximum heart rate not only was feasible and safe but also showed beneficial effects in QoL and physical functioning and maintained or at least improved fitness during concomitant chemotherapy [18]. Although not without bearing a considerably risk of bias, pooled data from another recent metaanalysis revealed that prehabilitation significantly improved mood, physical well-being, and immune function for prostate cancer patients and improved fatigue and psychological outcomes with a trend indicating better QoL among breast cancer patients [19].…”
Section: Introductionmentioning
confidence: 97%
“…A burgeoning body of research is investigating the utility of preoperative interventions, known as prehabilitation, to optimize posttreatment health outcomes. Numerous reviews of the prehabilitation literature in cancer populations demonstrate several important benefits, including improved preoperative and postoperative physical function, reduced hospital length of stay, and fewer postoperative complications (18)(19)(20)(21)(22)(23)(24). However, this literature exists almost exclusively in people undergoing tumor resection for thoracoabdominal malignancies, with breast cancer prehabilitation remaining largely unexamined.…”
Section: Introductionmentioning
confidence: 99%